Combined effect of dietary l‐carnitine and ractopamine supplementation on growth and nutritional composition of Labeo calbasu (Hamilton, 1822). (20th November 2021) - Singh, Ranjan; Das, Rakesh; Jain, Kamal Kant; Srivastava, Prem Prakash; Deo, Ashutosh D.
Abstract: The study determined the combined effect of dietary l ‐carnitine (non‐essential organic nutrient) and ractopamine (feed additive) on growth performance and nutritional composition of Labeo calbasu . To ascertain this, a 60‐day feeding trial was carried out under a controlled condition where two hundred and twenty‐five healthy L . calbasu fingerlings (avg. wt. 3.47 ± 0.1 g) were divided into four treatments group and one control group in triplicate. Therefore, the respective combination of l ‐carnitine and ractopamine diet was fed to L . calbasu fingerlings as C: control or basal feed without l ‐carnitine and ractopamine; T1:1 g kg −1 l ‐carnitine and 10 mg kg −1 ractopamine; T2: 2 g kg −1 l ‐carnitine and 20 mg kg −1 ractopamine; T3: 3 g kg −1 l ‐carnitine and 30 mg kg −1 ractopamine and T4: 4 g kg −1 l ‐carnitine and 40 mg kg −1 ractopamine, respectively. Upon completion of the 60‐day feeding experiment, eight fish were randomly collected from each tank and subjected to a series of laboratory analyses. The study determines that T2 group fish significantly ( p < .05) improved the WGP (244.66 ± 20.59%), SGR (0.89 ± 0.04), PER (2.20 ± 0.14) and increased crude protein content in fish muscle. In addition, many essential amino acids were recorded significantly high ( p < .05) in the fish fed with diet T2 compared with others. Hence, dietary supplementation of l ‐carnitine and ractopamine at 2 g kg −1 and 20 mg kg −1 in combination is beneficial for growth and nutritional composition of L. calbasu .